Estimation of the impact of genital warts on health-related quality of life. Issue 3 (13th March 2008) - Woodhall, S; Ramsey, T; Cai, C; Crouch, S; Jit, M; Birks, Y; Edmunds, W J; Newton, R; Lacey, C J N
Abstract : Objectives: One of the two new human papillomavirus (HPV) vaccines protects against HPV types 6 and 11, which cause over 95% of genital warts, in addition to protecting against HPV types 16 and 18. In anticipation of HPV vaccine implementation, the impact of genital warts on health-related quality of life (HRQoL) was measured to assess the potential benefits of the quadrivalent over the bivalent vaccine. Methods: Genitourinary medicine clinic patients aged 18 years and older with a current diagnosis of genital warts were eligible; 81 consented and were interviewed by a member of the research team. A generic HRQoL questionnaire, the EQ-5D (comprising EQ-5D index and EQ visual analogue scale (VAS) scores) and a disease-specific HRQoL instrument, the CECA10, were administered. Previously established UK population norms were used as a control group for EQ-5D comparisons. Results: Cases (with genital warts) had lower EQ VAS and EQ-5D index scores than controls. After adjusting for age a mean difference between cases and controls 30 years of age and under (n = 70) of 13.9 points (95% CI 9.9 to 17.6, p<0.001) for the EQ VAS and 0.039 points (95% CI 0.005 to 0.068, p = 0.02) on the EQ-5D index (also adjusted for sex) was observed. The difference between cases and controls for the EQ VAS was especially notable in young women. Conclusions: Genital warts are associated with a significant detriment to HRQoL. The potential added benefit of preventing most cases of genital warts by HPV vaccination should be considered in decisions about which HPV vaccine to implement in the United Kingdom.